Considering adjuvant therapy for stage II melanoma. Issue 6 (23rd December 2019) - Poklepovic, Andrew S.; Luke, Jason J.
Abstract : Melanoma is among the few cancers that demonstrate an increasing incidence over time. Simultaneously, this trend has been marked by an epidemiologic shift to earlier stage at diagnosis. Before 2011, treatment options were limited for patients with metastatic disease, and the median overall survival was less than 1 year. Since then, the field of melanoma therapeutics has undergone major changes. The use of anti–CTLA‐4 and anti‐PD1 immune checkpoint inhibitors and combination BRAF/MEK inhibitors for patients with BRAF V600 mutations has significantly extended survival and allowed some patients to remain in durable disease remission off therapy. It has now been confirmed that these classes of agents have a benefit for patients with stage III melanoma after surgical resection, and anti‐PD1 and BRAF/MEK inhibitors are standards of care in this setting. Some patients with stage II disease (lymph node‐negative; American Joint Committee on Cancer stage IIB and IIC) have worse melanoma‐specific survival relative to some patients with stage III disease. Given these results, expanding the population of patients who are considered for adjuvant therapy to include those with stage II melanoma has become a priority, and randomized phase 3 clinical trials are underway. Moving into the future, the validation of patient risk‐stratification and treatment‐benefit prediction models will be important to improve the number needed to treat and limit exposure to toxicity in the large population of patients with early stage melanoma. Abstract : Adjuvant therapy has improved outcomes in patients with stage III melanoma and is being explored in those with stage II melanoma. Stage III data as well as risk‐stratification tools and clinical considerations for the lymph node‐negative population are reviewed.